PENGARUH PENGUNGKAPAN AKUNTANSI MANAJEMEN LINGKUNGAN, BIAYA LINGKUNGAN, DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN SELAMA MASA PANDEMI - Silfadan Lafina Jaya Okta; Imarotus Suaidah; Dewi Wungkus Antasari (JCA (Jurnal Cendekia Akuntansi), 2022)
The purpose of this research is to find the influence of environmental management accounting disclosure, environmental cost, and environmental performance on firm value in the era of the COVID-19 pandemic. The population of this research is the manufacture companies on Indonesia Stock Exchange during the pandemic. Furthermore, this research is limited by using data from the pandemic from year 2020 to 2021. The used indicator to measure the firm value is Tobin’s ratio and the environmental performance indicator is using PROPER rating. The method used to analyze the influence of independent variable on the dependent variable in this research is multiple linear regression analysis and tested using the software SPSS 26.0, the result of the research show that the environmental management accounting disclosure and the environmental performance has significant and positive influence in the amount of 0,597. Furthermore, based on the simultaneous testing result, it is found that environmental management accounting disclosure, environmental cost, and environmental performance simultaneously influence the firm value by as big as 48,7%. Through this research, it is expected for companies, stakeholders, and the government to prioritize more and consider more about the environment for human survival. Keywords: Environmental Management Accounting Disclosure, Environmental Cost, Environmental Performance, Firm Value